2008
DOI: 10.2220/biomedres.29.205
|View full text |Cite
|
Sign up to set email alerts
|

Chick spinal accessory lobes contain functional neurons expressing voltagegated sodium channels generating action potentials

Abstract: Ten pairs of protrusions, called accessory lobes (ALs), exist at the lateral sides of avian lumbosacral spinal cords. Histological evidence has shown that neurons are present in AL and behavioral evidence suggests that AL acts as a sensory organ of equilibrium during bipedal walking. However, there is little functional evidence to indicate that cells in AL have neuronal functions. To elucidate this point, we developed a method to dissociate cells from chick AL and made electrophysiological recordings with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
(24 reference statements)
2
6
0
Order By: Relevance
“…The LSO presents a suite of features unique to the spinal column of birds, including bilateral protrusions of neural tissue identified as mechanosensors (accessory lobe (AL) neurons), located adjacent to ligaments supporting the spinal cord (Schroeder and Murray, 1987;Necker, 2005Necker, , 2006Yamanaka et al, 2008). The spinal cord is dorsally bifurcated in this region and supports a "glycogen body" (GB) centered on top.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LSO presents a suite of features unique to the spinal column of birds, including bilateral protrusions of neural tissue identified as mechanosensors (accessory lobe (AL) neurons), located adjacent to ligaments supporting the spinal cord (Schroeder and Murray, 1987;Necker, 2005Necker, , 2006Yamanaka et al, 2008). The spinal cord is dorsally bifurcated in this region and supports a "glycogen body" (GB) centered on top.…”
Section: Introductionmentioning
confidence: 99%
“…The arrangement of the canals, AL, ligaments, and GB is reminiscent of the vestibular system (Necker, 2006) and invites functional analogy to an accelerometer. Each AL contains mechanoreceptors (Schroeder and Murray, 1987;Necker, 2006;Yamanaka et al, 2008), with commissural axons projecting to last-order premotor interneurons in the spinal pattern generating network (Eide and Glover, 1996;Necker, 2006). The AL neurons within the LSO exhibit spontaneous firing and phase-coupled firing in response to vibrational stimulation between 75 and 100 Hz, and ablation of these neurons disrupts standing balance (Necker, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we found that enzymatically isolated cells from ALs of chick embryos showed depolarization-activated Na + current in the electrophysiological recording (18). In addition, it was reported that an intracellular concentration of Cl − in neuron-like cells isolated from chick embryonic ALs was as low as that of neurons of adult chicks (19), suggesting that a developing stage of neurons of chick embryos at E16-18 is similar to that of adult animals.…”
Section: Discussionmentioning
confidence: 90%
“…Subsequently, the supernatant was centrifuged again at 8,000 × g for 10 min rotransmitters exist in the ALs (9,12,13), there is little cellular evidence indicating that AL cells have neuronal functions. Previously, we reported that cells isolated from chick ALs showed voltage-gated Na + and K + currents under voltage-clamp conditions and generated action potentials under current-clamp conditions in whole-cell patch-clamp experiments (18). These results indicate that the voltage-gated Na + channel (VGSC) is expressed and that functional neurons generating action potentials exist in ALs.…”
mentioning
confidence: 74%
“…Rosenberg and Necker (2002) found dendritic projections of the accessory lobe neurons that extend into fluidfilled lacunae, analogous to the stereocilia of inner ear hair cells. Cells in the accessory lobes have neuronal-type voltage-gated sodium channels (Yamanaka et al, 2008, Matsushita et al, 2018, indicating the presence of neurons that can generate action potentials and are thus capable of acting as Necker suggests. In addition, there is evidence that implicates GABA (Yamanaka et al, 2012), glutamate (Yamanaka et al, 2013), and acetylcholine (Takahashi et al, 2015) in accessory lobe neuron function.…”
Section: A Mechanosensory Function For the Lsomentioning
confidence: 99%